SLEEP DISORDERS IN MENTALLY RETARDED CHILDREN - I. A. Kelmanson (Вопросы современной педиатрии, 2014)
The paper presents the study of the association between sleep disturbances and mental retardation in children. Attention is paid to the instant connection between sleep neurophysiology and intellectual progress, as well as between sleep disorders and the pathogenesis of mental retardation in children. The data on characteristic forms of sleep disturbances, including bed-time resistance, frequent night awakenings, parasomnias, abnormal sleep structure, and notably reduced REM-sleep proportion are provided. The potential role of abnormal melatonin production in the origins of sleep disturbances in children with mental retardation is discussed. Certain approaches to pharmacological and non-pharmacological corrections of sleep disorders are outlined.